ANALISIS PENGGUNAAN GAYA BAHASA PADA LIRIK LAGU DALAM ALBUM OPEN α DOOR KARYA AIMER (KAJIAN STILISTIKA) - Tasya Diana Maskuri; Muhammad Ali Hamdi; Dwi Astuti Retno Lestari (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2026)
This study aims to identify the use of language styles in the lyrics of Aimer's album Open α Door. This study is motivated by the use of language styles in Aimer's lyrics as a linguistic device that often hinders the listener to understand the hidden meaning behind the lyrics. Therefore, this study will analyze the use of language styles based on sentence structure and the directness of meaning in song lyrics. This study uses a qualitative approach with content analysis as the research method. Data collection techniques include observation followed by note-taking. The analysis technique employs the theory of Miles and Huberman (in Gunawan, 2022: 210). The theory used to identify types of language styles based on sentence structure and directness of meaning uses Keraf's theory (2007). Based on the analysis results, in the classification of types of stylistic devices based on sentence structure, the most dominant type of stylistic device is repetition. Then, in the classification of language styles based on the directness of meaning, the use of metaphors dominates. The use of this language style provides an aesthetic effect, strengthens emotional intensity, and brings the imagery in the song to life.